Comportamiento fisiológico y desarrollo vegetativo en plantas de café (Coffea arabica L.), en condiciones de campo, con cuatro niveles de sombra en San Antonio de las Aradas del cantón Quilanga - Felicito Alberca, Luis Enrique (2016)
This research was conducted in the Parroquia San Antonio de las Aradas del Cantón Quilanga of the Province of Loja, the objective was to contribute to the scientific and practical knowledge about the influence of shade on growth and physiological behavior of coffee. Shade levels that were evaluated were 0, 25, 50 and 75% levels maintained until the end of the evaluation. Evaluations were made monthly from the 166 days after transplant (DDT) variables were evaluated: plant height, number of branches plagiotropic, total number of leaves, leaf area, stomatal density; 174 to 342 DDT and DDT total chlorophyll content was determined and the 341 DDT total dry mass. The best results in terms of plant height, number of plagiotropic branches, total number of leaves, leaf area, stomatal density, total chlorophyll content and dry mass occurred in the treatment of 50% shade, in the case of stomatal density was best results in the treatment of full sunlight. Finally it was concluded that growth and vegetative growth of coffee plants expressed in indicators of plant height, number of plagiotropic branches, total number of leaves, leaf area and dry mass of plants showed a direct relationship with the shadow factor, just as the physiological indicators such as stomatal density, total chlorophyll content reacted to this factor; likewise the stomatal density was reflected in the treatment in full sunlight as this indicator is related to the size of the leaves exposed to full sunlight, have smaller area and therefore the concentration of stomata per mm2 is greater